On creating appropriate visual communication for the Tlicho community, stories, and culture ... - Raheel Malkan (University of Alberta Library, 2024)
In 2022, I began a creative collaboration with the Tlicho community, in the region of the Northwest Territories of Canada. As a visual communicator designer and researcher new to the country, I set out to help create an online tool for the Tlicho that would archive as well as visualize traditional Tlicho stories and their history. While I collected the stories for this project, I realized I did not know how to visually represent this community in a culturally appropriate manner. There exists a lot of Pan-Indian imagery and guidance on the web on how to represent indigenous cultures, however, very few projects take into account the different signs, motifs, and visual traditions that give each community its unique visual character. How does any particular First Nation “brand” language look different than a Métis way of visual communication? How can designers identify and use distinct visual systems to create imagery for different Indigenous nations? This question is at the center of my thesis. To address this ...